In vitro effects of cyanobacteria (Oscillatoria tenuis) extracellular products on date palm (Phoenix dactylifera L. cv. ‘Barhee’) propagation - Majid Ibrahim (Dysona. Applied Science, 2021)
This study was conducted to investigate the effect of the medium type (half-strength MS medium and MS free medium) and the extracellular products of cyanobacteria (Oscillatoria tenuis) that were grown under photoperiods of 8 or 16 h day-1 on the shoot proliferation and rooting of in vitro ‘Barhee’ date palm ciltures. MS free medium failed to establish half-strength MS medium results, which indicates that the medium could not sustain cultures requirments during shoot proliferation and rooting phase. On the other hand, half-strength MS medium supplemented with extracellular products of O. tenuis grown at 16 h day-1 photoperiod recorded the best results in regards of response to direct organogenesis and rooting.